2017
DOI: 10.1371/journal.pone.0176185
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of per sample global scaling and per gene normalization methods for differential expression analysis of RNA-seq data

Abstract: Normalization is an essential step with considerable impact on high-throughput RNA sequencing (RNA-seq) data analysis. Although there are numerous methods for read count normalization, it remains a challenge to choose an optimal method due to multiple factors contributing to read count variability that affects the overall sensitivity and specificity. In order to properly determine the most appropriate normalization methods, it is critical to compare the performance and shortcomings of a representative set of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 51 publications
4
64
0
Order By: Relevance
“…Previous assessments of RNA-seq normalization methods have usually found that common, widely used methods perform well [2][3][4][5][6]. I show here that this is not the case when challenging normalization tasks are considered, suggesting that previous tests may have been overly simplistic.…”
Section: Introductionmentioning
confidence: 59%
“…Previous assessments of RNA-seq normalization methods have usually found that common, widely used methods perform well [2][3][4][5][6]. I show here that this is not the case when challenging normalization tasks are considered, suggesting that previous tests may have been overly simplistic.…”
Section: Introductionmentioning
confidence: 59%
“…Since this study has been recently published, the normalized MAQC2 data from Med-pgQ2, UQ-pgQ2, DESeq and TMM-edgeR and DEGs analysis from these methods can be downloaded in Supporting Information S2-S5 Datasets [81]. Moreover, these normalization methods are written in R (v3.1.3) with the source codes publically available in S1 File (.R) [81]. …”
Section: Software Packages For Detecting Degs In Normalization Methodsmentioning
confidence: 99%
“…DESeq and TMM normalization methods were implemented using DESeq2 and edgeR packages. UQ-pgQ2 normalization was implemented using R [17,18,81].…”
Section: Normalization Methodsmentioning
confidence: 99%
See 2 more Smart Citations